Divergent Perspectives on Learner Engagement in Adult Literacy Classrooms - Anastasiya A. Lipnevich (Adult Education Research Conference, 2007)
This roundtable will focus on two types of quantitative data that measures the engagement of learners in adult literacy classrooms and the ways in which educational roles dramatically affect perceptions of classroom behaviors.